1985
DOI: 10.1002/gepi.1370020403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of household sharing on high density lipoprotein and its subfractions

Abstract: Household effects accounted for significant proportions of the observed variance of high density lipoprotein cholesterol (HDL-C) and subfractions HDL2 and HDL3. It was found that 19.3% of HDL-C variance could be attributed to a juvenile sib effect (under age 18); 17.4% of HDL2 variance could be attributed to a sib effect (of any age); and 22.1% and 32.6% of the HDL3 variance could be attributed to a parent-offspring effect and a sib effect (of any age), respectively. In addition, additive genetic effects accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A young, healthy population will have less environmental variance due to age and lack of disease processes than an older and ill sample; thus, the relative contribution of genetic variance will be larger, resulting in larger heritability estimates. Previous heritability estimates have been higher for HDL 2 than for HDL 3 (32,33). However, a previous study reported highest parent‐offspring correlations for HDL 2b but highest sibling correlations for HDL 3b (34), which agrees well with our result of quite high heritability estimates for both large and small HDL.…”
Section: Discussionmentioning
confidence: 93%
“…A young, healthy population will have less environmental variance due to age and lack of disease processes than an older and ill sample; thus, the relative contribution of genetic variance will be larger, resulting in larger heritability estimates. Previous heritability estimates have been higher for HDL 2 than for HDL 3 (32,33). However, a previous study reported highest parent‐offspring correlations for HDL 2b but highest sibling correlations for HDL 3b (34), which agrees well with our result of quite high heritability estimates for both large and small HDL.…”
Section: Discussionmentioning
confidence: 93%
“…The indices used to measure shared familial environment in these studies, information on smoking and alcohol habits, body mass, and socioeconomic levels, are acknowledged to be crude and inadequate; measures of between-family differences in diet, physical activity patterns, or stress exposure, relevant to individual variation in lipoproteins, have not been attempted, but direct evidence of the influence of shared household experience on HDL-C has been found in the higher correlations of siblings and parent—offspring pairs when the siblings (and offspring) are younger than 20 years of age than when they are older and no longer sharing household experience (Morrison et al, 1982). Household effects shared by juvenile siblings accounted for nearly 20% of the variance in HDL-C in a sample of over 2,000 Utah family members (Hasstedt, Kuida, Ash, & Williams, 1985). Such estimates of environmental effects on HDL-C are in contrast to the negligible estimate (2.9%) yielded by typical MZ—DZ twin data, although the twin estimates were based on a path analytic model similar to those used in the family studies (Coletto, Krieger, & Magalhaes, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…GWA studies and Mendelian randomization studies have suggested that genetic mechanisms that raise plasma HDL-C do not seem to lower risk of MI [38]. However, based on family and twin studies, HDL-C levels have shown a heritability ranging from 40 to 60 % [39,40]. Recent GWA studies have shown that only 10-12 % of the heritability is due to common variants [41,42], suggesting that a large proportion of the molecular mechanisms underlying HDL-C functions and metabolism is still unknown.…”
Section: Hdl Metabolism Pathwaymentioning
confidence: 99%